2012
DOI: 10.1155/2012/340380
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal of a Practical and Optimal Prophylactic Strategy for Peritoneal Recurrence

Abstract: Peritoneal metastasis, which often arises in patients with advanced gastric cancer, is well known as a miserable and ill-fated disease. Once peritoneal metastasis is formed, it is extremely difficult to defeat. We advocated EIPL (extensive intraoperative peritoneal lavage) as a useful and practical adjuvant surgical technique for those gastric cancer patients who are likely to suffer from peritoneal recurrence. In this paper, we review the effect of EIPL therapy on prevention of peritoneal recurrence on patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
(39 reference statements)
1
20
0
Order By: Relevance
“…According to their pioneering studies that far exceeded any expectations and showed a remarkably better prognosis for patients suffering of advanced gastric cancer (C1P0) (2,4) , these authors have strongly advocated the adoption of EIPL therapy for patients with positive peritoneal washing cytology with no overt peritoneal carcinomatosis, and for all patients with serosa-involved gastric cancer or lymph node metastases, regardless of their cytological status (1,3) . In these settings, Yu et al (5) similarly presented the potential value of EIPL for decreasing the risk of peritoneal metastasis in patients with locally advanced stages who underwent D2-gastrectomies, and a randomized phase III trial (CCOG 1102) exploring the prognostic value of EIPL in addition to standard treatment for resectable advanced gastric cancer has started in Japan (UMIN Clinical Trials Registry: UMIN000005907).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to their pioneering studies that far exceeded any expectations and showed a remarkably better prognosis for patients suffering of advanced gastric cancer (C1P0) (2,4) , these authors have strongly advocated the adoption of EIPL therapy for patients with positive peritoneal washing cytology with no overt peritoneal carcinomatosis, and for all patients with serosa-involved gastric cancer or lymph node metastases, regardless of their cytological status (1,3) . In these settings, Yu et al (5) similarly presented the potential value of EIPL for decreasing the risk of peritoneal metastasis in patients with locally advanced stages who underwent D2-gastrectomies, and a randomized phase III trial (CCOG 1102) exploring the prognostic value of EIPL in addition to standard treatment for resectable advanced gastric cancer has started in Japan (UMIN Clinical Trials Registry: UMIN000005907).…”
Section: Discussionmentioning
confidence: 99%
“…In these settings, an extensive peritoneal washing might flush out the free cancer cells in the peritoneal cavity and has been proposed as a practical approach to decrease the risk of peritoneal metastasis (1,3) . Applying this formidable method for reducing the number of free cancer cells to potentially zero, namely Extensive Intraoperative Peritoneal Lavage (EIPL), a remarkably better prognosis has been shown for Asian patients suffering of gastric cancer (2,4,5) .…”
Section: A Phase II Trial Exploring the Extensive Intra-operative Permentioning
confidence: 99%
See 1 more Smart Citation
“…There was also no significant difference in peritoneal recurrence rates, i.e., 13 (35.1%) in the CY1/P0 group and 5 (21.7%) in the stage III B + C group (P = 0.39). Conclusions EIPL therapy combined with complete resection and sufficient (D2) lymphadenectomy could cancer cells to potentially zero [10][11][12]. We have previously reported that EIPL therapy remarkably improved the survival rate of CY1/P0 advanced gastric cancer patients after curative surgery [12].…”
Section: Introductionmentioning
confidence: 88%
“…The type of gastrectomy, such as distal or total gastrectomy, was based on the location or the status of the primary tumor extension. D2 lymphadenectomy, gross R0 resection, and EIPL therapy were performed for all cases [11]. The procedure for EIPL therapy was as follows.…”
Section: Surgery Eipl Therapy and Adjuvant Therapymentioning
confidence: 99%